Development of a Novel Remote Patient Monitoring System: The Advanced Symptom Management System for Radiotherapy to Improve the Symptom Experience of Patients With Lung Cancer Receiving Radiotherapy. Issue 2 (March 2015) - Maguire, Roma; Ream, Emma; Richardson, Alison; Connaghan, John; Johnston, Bridget; Kotronoulas, Grigorios; Pedersen, Vibe; McPhelim, John; Pattison, Natalie; Smith, Allison; Webster, Lorraine; Taylor, Anne; et al.
Abstract : Background: The use of technology-enhanced patient-reported outcome measures to monitor the symptoms experienced by people with cancer is an effective way to offer timely care. Objective: This study aimed to ( a ) explore the feasibility and acceptability of the Advanced Symptom Management System with patients with lung cancer receiving radiotherapy and clinicians involved in their care and ( b ) assess changes in patient outcomes during implementation of the Advanced Symptom Management System with patients with lung cancer receiving radiotherapy in clinical practice. Methods: A repeated-measures, single-arm, mixed-methods study design was used involving poststudy interviews and completion of patient-reported outcome measures at baseline and end of treatment with 16 patients with lung cancer and 13 clinicians who used this mobile phone–based symptom monitoring system. Results: Only rarely did patients report problems in using the handset and they felt that the system covered all relevant symptoms and helped them to manage their symptoms and effectively communicate with clinicians. Clinical improvements in patient anxiety, drowsiness, and self-care self-efficacy were also observed. Clinicians perceived the use of "real-time" risk algorithms and automated self-care advice provided to patients as positively contributing to clinical care. Reducing the complexity of the system was seen as important to promote its utility. Conclusions: Although preliminary, these results suggest that monitoring patient symptoms using mobile technology in the context of radiotherapy for lung cancer is feasible and acceptable in clinical practice. Implications for practice: Future research would be most beneficial if the use of this technology was focused on the postradiotherapy phase and expanded the scope of the system to encompass a wider range of supportive care needs.